PROGRAM-ORIENTED AND GOAL-ORIENTED APPROACH TO RESEARCH PLANNING - Vasily N. Popov (Высшее образование в России)
The article analyzes the program-oriented and goal-oriented approach used to enhance Voronezh State University's advanced world-class level research and development and faster growth of human resource capacity and the university facilities. It also reviews the processes of information technologies introduction into the main fields of the university activities. Additionally, it discusses research support mechanisms and the university target programme results.